Intergroup contact as a tool for reducing, resolving, and preventing intergroup conflict: evidence, limitations, and potential. - Al Ramiah, A; Hewstone, M (2013)
We propose that intergroup contact provides an effective means by which to reduce, resolve, and prevent conflict of all kinds, including violent conflict. We review the vast literature on the effectiveness of intergroup contact and discuss when and how it reduces prejudice. We also discuss key features of successful interventions, highlighting examples from conflict zones around the world. Rather than accepting, as some scholars do, that conflict is inevitable, we argue that intergroup contact, in its various forms, can play a pivotal and preemptive role in conflict prevention. We suggest that a blunt application of contact theory, particularly when groups are of unequal status, can have some unfortunate consequences, and contact interventions can, and should, be designed to overcome these pitfalls. We argue that, ultimately, contact is a powerful tool that needs to be used alongside other means of conflict reduction, resolution, and prevention in order to frame sound public policy and build lasting peace.